Social connectedness, collaborative learning and student performance in an academic development programme - Patsika, Natasha (Organisational Psychology, 2016)
This study investigated the relationship between social connectedness, collaborative learning and the academic performance of students in an academic development (AD) programme at a South African university. A final sample of 119 students responded to a survey questionnaire containing the campus connectedness scale and the collaborative learning scale, each measured on a six-point Likert scale. A multiple regression analysis revealed that social connectedness is a significant predictor of academic performance, which was measured using grade point average (GPA). The study found that collaborative learning did not contribute to variations in GPA, however it did relate positively to social connectedness. The results provide useful information to staff in the AD programme about elements of the programme that are succeeding in supporting student achievement. Includes bibliographical references (pages 49-54).